WhatsApp disruptions in Brazil: A content analysis of user and news media responses, 2015–2018. (April 2022) - Pereira, Gabriel; Bueno Bojczuk Camargo, Iago; Parks, Lisa
Brazilians have adopted WhatsApp as a national media and communication infrastructure over the past several years, although it is controlled by its private US-based owner, Facebook. This article explores the diverse, contentious and influential roles the app played in the country during disruptions to its use from 2015 to 2018. Using content analysis, we critically engage with user-generated memes and news media coverage responding to these disruptions. In these cases, Brazilians self-reflexively questioned the app's role in their everyday lives and country, reassessing what it means to rely on a national infrastructure owned by an unaccountable global media conglomerate.